2023
DOI: 10.3389/fimmu.2023.1161273
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated ESRP1/2 promotes lung metastasis of bladder carcinoma through altering FGFR2 splicing and macrophage polarization

Abstract: IntroductionLung metastasis occurs in parts of the bladder carcinoma (BC) patients but represents the highest severity and a poor outcome of the disease. The molecular mechanism underlying lung metastasis of BC is not fully understood. Fibroblast growth factor receptor 2 (FGFR2) signaling plays a substantial role in the BC cell growth and invasion. In this study, we assessed the regulation of the alternative splicing of FGFR2 by epithelial splicing regulatory proteins (ESRPs) in lung metastasis of BC.MethodsGe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A study has shown that AS is connected with the proliferation and invasion of cancer cells ( 19 ). Different types of ASEs and polarization of macrophages can promote metastasis of lung cancer ( 20 ). High expression of COLIA1 can promote the proliferation and metastasis of cervical cancer cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that AS is connected with the proliferation and invasion of cancer cells ( 19 ). Different types of ASEs and polarization of macrophages can promote metastasis of lung cancer ( 20 ). High expression of COLIA1 can promote the proliferation and metastasis of cervical cancer cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…High ESRP2 expression associated with lymph node metastasis ( p < 0.0001) has been reported in prostate cancer [ 64 ]. In bladder cancer, a high level of ESRP2 expression has been linked to lung metastasis ( p < 0.0001) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ESRP1 was found to decrease the migration and invasion of gastric cancer cells, suggesting the tumor-suppressive role of ESRP1. Furthermore, ESRP1 reduction promoted tumor growth and lung metastasis of bladder cancer in vivo [ 18 ]. However, the prognostic significance and role of ESRP1 in bladder, cervical, gastric, and renal cancers are unclear and need to be further investigated.…”
Section: Dual Role Of Esrp1 In Cancer Progressionmentioning
confidence: 99%
“…Another study reported the effect of ESRP1 on tumor-associated macrophages in the TME. ESRP1 inhibited tumor growth and lung metastasis in xenograft mouse model of bladder cancer, and also promoted the polarization of tumor-associated macrophages into anti-tumor phenotype in vivo [ 18 ]. This suggests that ESRP1 plays a tumor-suppressive role in bladder cancer in part by its effect on macrophage polarization.…”
Section: Emerging Roles Of Esrp1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation